Becoming a Virtual Cutie: Digital Cross-Dressing in Japan. (December 2022) - Bredikhina, Liudmila; Giard, Agnès
There is a predominance for cute characters among Japanese virtual YouTubers (VTubers). Men who publicly use feminine avatars to conduct online entertainment are called babiniku in Japan. This research paper investigates whether embodying cute avatars impacts males' perception of self. Examining the process leading some online performers to turn into outwardly feminine characters, we address the reasons why babiniku reproduce gender stereotypes. Our presumption is that such role play is part of a strategy with purposes yet to be deciphered. We deployed quantitative and qualitative methods, such as survey and semi structured interviews, to collect first-hand testimonies from 24 babiniku participants. This article contributes to an existing literature about digital gender swapping with avatars and Japanese cross-dressing from an anthropological perspective. As stressed by the babiniku who took part in this research, digital cross-dressing enables them to create a world where they can indulge in fancy and fantasy. All together with their fans, babiniku build a notion of femininity that allows users to act and live outside of societal pressures.